Determination of Iron (Fe) and Copper (Cu) on Pellets from Fermentation of Mozambique Tilapia (Oreochromis mossambicus) using Goat Dirt Adhesives - Verren T. M. Pariama; Paulus H. Abram (Universitas Tadulako, 2020)
Tilapia fish waste and livestock manure are an environmental problem, besides being smelly pollution will also cause disease disorders for humans. The purpose of this study was to determine the levels of micronutrients of iron (Fe) and copper (Cu) on pellets from the fermentation of waste tilapia (oreochromis mossambicus) using adhesive goat manure. Fish waste was fermented for 15 days and mixed with adhesive goat manure and then was processed in a pellet making machine. The Fe and Cu levels were determined using Atomic Absorption Spectrophotometer (AAS). The results of the determination of levels Fe was 137 ppm and for Cu was 4.1 ppm.